The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/met9121312
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Central Carbon Segregation in Continuous Casting Billet Using A Regularized Extreme Learning Machine Model

Abstract: Central carbon segregation is a typical internal defect of continuous cast steel billets. Real-time and accurate carbon segregation prediction is of great significance for lean control of the production quality in continuous casting processes. In this paper, a data-driven regularized extreme learning machine (R-ELM) model is proposed for the prediction of carbon segregation index (CSI). To improve model performance, outliers in industrial data were eliminated by means of boxplot tool. Besides, Pearson correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The results indicated that the model was suitable for a complex hot-rolling process. Zou et al [13] established a carbon segregation prediction model for CC billets based on the regularized ELM (RELM) algorithm, by comparing it with multiple linear regression and the classical ELM model. The results showed that the RELM model had better prediction accuracy and generalization ability.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the model was suitable for a complex hot-rolling process. Zou et al [13] established a carbon segregation prediction model for CC billets based on the regularized ELM (RELM) algorithm, by comparing it with multiple linear regression and the classical ELM model. The results showed that the RELM model had better prediction accuracy and generalization ability.…”
Section: Related Workmentioning
confidence: 99%
“…Effective quality prediction can improve the final slab quality, save energy consumption, and stabilize the production. Several machine learning algorithms have been widely used by scholars in the field of CC to construct excellent quality prediction models, such as: random forest (RF) [8], [9], support vector machine (SVM) [10], [11], and artificial neural networks, especially extreme learning machine (ELM) [12], [13]. Nevertheless, most studies ignore the natural class imbalance in CC datasets that the number of normal slabs is much more than that of abnormal slabs.…”
Section: Introductionmentioning
confidence: 99%
“…Rejection of elements from the solid phase leads to an increase in the residual melt and consequently to a positive microsegregation. [ 31–33 ] The primary solidification in steel castings can be columnar dendritic, equiaxed dendritic, or globular, depending on the boundary conditions. [ 34–37 ] During dendritic solidification, the microsegregated melt gets captured between the dendritic arms.…”
Section: Reduction Of Cross‐sectional Area and Ductility Influencing ...mentioning
confidence: 99%
“…Varfolomeev et al [26] and Ye et al [27] used the random forest algorithm to predict crack occurrence in the continuous casting billets. Furthermore, researchers, including the author, have also applied AI algorithms to predict central carbon segregation in continuous casting billets [28][29][30]. However, the previous studies only assessed whether cracks would occur (two-category problem) or determined the probability of cracks.…”
Section: Introductionmentioning
confidence: 99%